2006
DOI: 10.1016/j.ejvs.2005.08.007
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Differential Expression of Extracellular Matrix Metalloproteinase Inducer, Matrix Metalloproteinase-2, Tissue Inhibitor of Matrix Metalloproteinase-2 and PDGF-AA on the Chronicity of Venous Leg Ulcers

Abstract: Non-healing venous ulcers are associated with greater activity MMP-2 activity. The ratio of MMPs to their inhibitors TIMPs, dictate the rate of healing of the ulcers. PDGF-AA activity is associated with ulcer healing, though the mechanism is unclear. EMMPRIN expression in chronic venous ulcers probably parallels the chronicity of the condition rather than propagate it. However, further studies with larger samples are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0
7

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 94 publications
(82 citation statements)
references
References 24 publications
3
72
0
7
Order By: Relevance
“…Cytokines demonstrating no distinct differences at the different time-points were sTNFR-I (also known as p55) and Tissue Inhibitor of Metalloproteinase-2 (TIMP-2) consistent with previous studies [28]. IL-6R levels decreased in non-healing wounds from week 0 to week 4 with an increase again from week 4 to week 8.…”
Section: Cytokine Profiles In Wound Fluids From Chronic Venous Leg Ulsupporting
confidence: 79%
“…Cytokines demonstrating no distinct differences at the different time-points were sTNFR-I (also known as p55) and Tissue Inhibitor of Metalloproteinase-2 (TIMP-2) consistent with previous studies [28]. IL-6R levels decreased in non-healing wounds from week 0 to week 4 with an increase again from week 4 to week 8.…”
Section: Cytokine Profiles In Wound Fluids From Chronic Venous Leg Ulsupporting
confidence: 79%
“…It has been implied that the ratio between MMPs and TIMPs is important in wound healing and TIMPs might participate in the tissue-repair process [26]. Two recent studies have demonstrated that high levels of MMP2 and low levels of TIMP-1 and TIMP-2 are associated with non-healing venous leg ulcers [42] and with gastric ulceration induced by ethanol [43]. Taken together, these data and our findings indicate another imbalance of MMP2 and TIMPs in ulceration and impaired healing.…”
Section: Discussionsupporting
confidence: 66%
“…Ladwig et al (Ladwig et al 2002) and Liu et al (Liu et al 2009) reported an increased ratio of MMP-9 to TIMP-1 in chronic nonhealing wound fluid compared with healing wounds. Together with the finding that the MMP2:TIMP-2 ratio is elevated in non-healing compared with healing leg ulcers (Mwaura et al 2006), this suggests that a disturbed homeostasis between MMPs and TIMPs might be correlated with the non-healing status. Also, in chronic non-healing diabetic foot ulcers, MMPs and their inhibitors (TIMPs) have received much interest.…”
Section: Proteases and Their Inhibitorsmentioning
confidence: 83%